Asphalt Rideability Specification and Construction of Expressways in Qatar - Hodgson, Roger James; Kara, Ali (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Development of an Expressway network with a smooth ride quality is part of the Qatar 2030 Vision. The Public Works Authority (Ashghal) has placed high importance on the asphalt specification and quality of construction of the Expressway network to produce a perceived smooth, uninterrupted ride quality for the benefit of the traveling public. Ashghal has used a robust international specification for the International Roughness Index (IRI) and has required the Contractors and Supervision Consultants on the Expressway projects to produce an exceptional ride quality by training asphalt paving crews, using state-of the art asphalt paving and levelling equipment and quality control testing of the finished pavement. Various obstacles have been encountered in the Ashghal quest to produce world-class asphalt pavements and those obstacles have been overcome. This paper highlights the lessons learned from asphalt construction and aims to deliver to a wider audience the benefits of the Ashghal experience.